Psychological features of mental states’ self-regulation of young basketball players - Rochniak, Anton (NTU "KhPI", 2018)
The article reviews features of mental states dynamics of young basketball players before, during and after competitions in connection with various indicators of sports activity self-regulation. It also contains the statistical analysis results of functional states indicators comparisons between groups with different self-regulation of sports activity. It was shown that the nature of changes in the functional state and its peculiarities in the young basketball players is determined by indicators of sports self-regulation.

У статті розглядаються особливості динаміки психічних станів молодих баскетболістів до, під час та після змагань у зв'язку з різними показниками саморегуляції спортивної активності. Дослідження містить результати статистичного аналізу порівняльних показників функціональних станів між групами з різною саморегуляцією спортивної активності. Показано, що характер змін у функціональному стані та його особливості у молодих баскетболістів визначаються показниками спортивної саморегуляції.
Психологічні особливості самоврядного регулювання молодих баскетболістів
Keywords: mental state; self-regulation; functional state; young basketball players; state of health; activity; mood; dynamics; психічний стан; саморегуляція; функціональний стан; молоді баскетболісти; стан здоров'я; активність; настрої; динаміка